Cotton bollworm in the Philippines a review - Pascual, Leonardo T.; Van Huis, Arnold; Van Lenteren, Joop C. (1997)
The cotton bollworm, Helicoverpa is one of the most serious pests in cotton. Helicoverpa can reduce seedcotton yield by 37 to 92% and cotton farmers spend 35 to 47% fo their cash cost to control it. There have been deliberate attempts to develop control strastegies towards effective mangement of this pest. Information available about Helicoverpa in cotton in the Philippines is review in this paper. Its taxonomy, morphology, life history, life ecology, phenology, economic importance, control measures and natural enemies are discussed.
Keywords: Pests